THE EFFECTIVENESS OF COMPUTER SIMULATION-BASED LEARNING FOR MASTERING FORCE AND MOTION CONCEPTS AMONG SECONDARY SCHOOL STUDENTS FORM FOUR PHYSICS - Nurul Iman Hanisah Binti Azmi; Fatin Aliah Phang (Joint Prosiding IPS dan Seminar Nasional Fisika, 2026)
Force and Motion is among the difficult topics for students to learn in Physics because of the abstract concepts and the ability for the students to visualize the concepts. Computer simulations could be a solution for the students to learn this topic to help the students to visualize the concepts. Therefore, this study aims to evaluate the effectiveness of computer simulations in enhancing students’ conceptual mastery of force and motion. The study was conducted in response to low student achievement in physics, particularly when traditional teaching methods are used. A quasi-experimental design with a one-group pretest-posttest model was implemented, involving 37 students from two secondary schools in Malaysia. The intervention involved simulation-based lessons using PhET tools. Data were collected using a test with 11 multiple choice items and analysed using descriptive statistics and a paired-sample t-test. The findings revealed a significant improvement in students’ post-test scores (M = 76.66%) compared to their pre-test scores (M = 32.68%), with a statistical significance of p < .001. The result indicates that simulation-based instruction effectively enhances students’ understanding of abstract physics concepts and supports the goals of Malaysia’s Digital Education Policy in integrating technology into physics education.